Guidance on prevention of viral hepatitis B and C among people who inject drugs (World Health Organization, 2012)
A World Health Organization practical guidance that focuses on viral hepatitis B and C surveillance, prevention and treatment. Intended for professional public.
HIV/AIDS Programme
Keywords: Drug Users; hepatitida C; uživatelé drog; veřejné zdravotnictví; intravenózní abúzus drog; Disease Transmission, Infectious; Primary Prevention; rizikové faktory; Hepatitis C; hepatologie; Risk Factors; Substance Abuse, Intravenous; hepatitida B; Hepatitis B; primární prevence; preventivní medicína; přenos infekční nemoci